Subjective complaints of memory, objective performance and related neuropsychological functions. A systematic review - Carlos Mias; Belen Causse (Perspectivas Metodológicas​)
A systematic review analyzes the relationship of Subjective Memory Complaints (SMC) with objective performance in tests of memory and other functions, and their implications on cognitive impairment. Using the PRISMA NMA methodology, 23 articles were selected from the PubMed database, with a total of 21,445 older adults evaluated. In 65% a relationship between SMC and changes in memory measurement was identified and in 56% in executive functions, although only in 22% it was associated with cognitive impairment. Modulating variables are identified, such as depression and other psychological ones. 73.91% of the studies recommend attending SMC in older adults, considered a risk variable, increasing its value in combination with objective measures of neuropsychological functions.